Pemberdayaan Kelompok Tani Hutan Adian Nasonang dalam Budidaya Ternak Lebah Trigona untuk Meningkatkan Ekonomi Masyarakat - Sri Hartini; Marzuki Ahmad; Perima Simbolon; Sri Rahmi Tanjung; Muhammad Syahril Harahap (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2025)
This community service initiative aims to enhance the production and management of Trigona honey bee culture as an alternative economic resource within the Adian Nasonang Forest Farmers Group (KTH). This initiative aims to enhance KTH Adian Nasonang by augmenting the technical and managerial capabilities of Trigona bee cultivation. This issue was addressed through a Participatory Action Research (PAR) approach, which positions the partner community as an active participant in every phase of the activity. The activity involved members of KTH Adian Nasonang. The conducted activities demonstrated an enhancement in partners' comprehension of Trigona honey bee cultivation, as evidenced by the rise in the baseline questionnaire score from 53.35 to the final score of 82.94. In other terms, there was a 61.02% increase in the moderate group. The activity's outcomes indicated an enhancement in partners' comprehension of Trigona bee culture, maintenance methodologies, and safe, efficient harvesting practices. Furthermore, there was an enhancement in the group's motivation and preparedness to pursue apiculture as an alternative revenue stream. This community service initiative has effectively enhanced the knowledge, abilities, and preparedness of KTH Adian Nasonang in the cultivation of Trigona bees, hence potentially bolstering the community's income sources.